Reading 1 Cor 11:19 in Light of Election Practices in Private Associations - Lee, Jin Hwan; De Wet, Chris L. 1982- (2020)
In 1 Cor 11:19, Paul talks about hoi dokimoi faneroi (“the distinctively approved ones”) among the Christ group in Corinth. Paul mentions these people in a context in which he criticises factions and divisions in the group. The verse itself is not enough to understand what the group practiced in advance to have such approved members, nor are we aware of how the group proceeded with the practice and what the prerequisites were. This article attempts to answer these crucial questions by examining association data from ancient Greece regarding election procedures to understand 1 Cor 11:19 within its particular social context, and the Christ group in Corinth in general.
Keywords: hairesis; 1 Cor 11:19; private associations; commendation; honorific inscriptions; Elections